Implementasi Manajemen Pendidikan Karakter Di Sekolah - Mujahidatun Mukhlisoh; Suwarno Suwarno (IAI Darussalam, 2019)
Character is a matter that needs attention in the world of education. Character is a system that underlies a person's thoughts and behavior. So, it can be said that without a strong foundation of character values ​​will make education and the fragility of the young generation of a nation low. In general, this study aims to find and disclose planning, implementation, organizing, evaluating, constraints and solutions in overcoming the constraints of character education implementation. The research method used in this study is a qualitative research design with multi cases of research conducted at two institutions, namely at SDI Raudlatul Jannah Sidoarjo and SD Al-Hikmah Surabaya in a management review with the characteristics of different research objects. The results of the study found SDI Raudlatul Jannah Sidoarjo and Al-Hikmah Elementary School Surabaya, both of them together form a character education program by carrying out stages of management functions effectively. The effectiveness of the planning is evident from the stages of the planning process carried out by the school by preparing a strategic plan for character education